Sensorimotor Incongruence and Body Perception: An Experimental Investigation - Foell, Jens; Bekrater-Bodmann, Robin; McCabe, Candida S.; Flor, Herta (Frontiers in Human Neuroscience, 2013)
Objectives: Several studies have shown that mirrored arm or leg movements are related to altered body sensations. This includes the alleviation of chronic pain using congruent mirror feedback and the induction of abnormal sensation in healthy participants using incongruent mirror feedback. Prior research has identified neuronal and conceptual mechanisms of these phenomena. With the rising application of behavior-based methods for pain relief, a structured investigation of these reported effects seems necessary. Methods: We investigated a mirror setup that included congruent and incongruent hand and arm movements in 113 healthy participants and assessed the occurrence and intensity of unusual physical experiences such as pain, the sensation of missing or additional limbs, or changes in weight or temperature. A wooden surface instead of a mirror condition served as control. Results: As reported earlier, mirrored movements led to a variety of subjective reactions in both the congruent an incongruent movement condition, with the sensation of possessing a third limb being significantly more intense and frequent in the incongruent mirror condition. Reports of illusory pain were not more frequent during mirrored than during non-mirrored movements. Conclusions: These results suggest that hand movements with and without a mirror induce abnormal body perceptions but that the experience of an extra limb is most pronounced in the incongruent mirror movement condition. The frequent sensation of having a third arm may be related to brain processes designed to integrate input from several senses in a meaningful manner.